Designing an integrated model for innovative goods order fulfillment in a assemble-to-order system considering uncertainty in demand - Babak Javadi; Sasan Taslimi; Niloofar Abdolmaleki (مدیریت مهندسی و رایانش نرم)
In this study, we focus on the production of innovative goods facing uncertain demand within an order-based assembly system featuring multiple products and periods. Originating from a manufacturer of automation products and precision instruments, the production processes are categorized into three types: inflexible, flexible, and final assembly. In-house execution of inflexible and final assembly processes is crucial for retaining technical expertise and ensuring quality standards. Flexible processes, however, are typically outsourced to expedite order delivery and enhance production capacity. Yet, if excess capacity exists, these processes can be conducted internally alongside inflexible operations. To optimize profit and meet order requirements effectively, we propose an integrated model that considers production constraints. This model encompasses decision-making regarding order acceptance/rejection, production planning, and scheduling. Employing a robust optimization approach, we address the uncertainty inherent in demand variations. We then linearize the model and utilize optimization software to solve it across small and medium dimensions, considering various uncertainty levels. Through analysis of the results, we demonstrate the model's efficiency and underscore the benefits of incorporating production flexibility.